The Self-Avatar Follower Effect in Virtual Reality - Gonzalez Franco, Mar; Cohn, Brian; Burin, Dalila; Ofek, Eyal; Maselli, Antonella (IEEE VR 2020, 2020)
When embodying a virtual avatar in immersive VR applications, users typically are and feel in control the avatar movements. However, there are situations in which the technology could flip this relationship so that an embodied avatar could affect the user's motor behavior without users noticing it. This has been shown in action retargeting applications and motor contagion experiments. Here we discuss the self-avatar follower effect. We review previous evidences and present new experimental results showing how, whenever the virtual body does not overlay with their physical body, users tend to unconsciously follow their avatar, filling the gap if the system allows for it.